1982
DOI: 10.1139/v82-205
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation des pièges à radicaux en vue de mettre en évidence des intermédiaires dans la photolyse de complexes contenant une liaison CoIII—C

Abstract: Using the spin trapping technique with 5,5′-dimethyl 1-pyrroline N-oxide (DMPO), phenyl-N-tert-butyl nitrone (PBN), nitrosodurene (ND), and α-4-pyridyl 1-oxide N-tert-butl nitrone (4-POBN), or their mixtures, we have been able to detect two types of radicals, one is a hydrogen atom spin adduct and the other is the corresponding alkyl of the alkylcobaloximes, salens or cobalamines.By the use of selective deuteration and the preparation of the benzyl bis(diphenylglyoximato)-pyridinato cobaloxime, we have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The cleavage of the cobalt−carbon bond, which is a central issue in B 12 chemistry, has been studied in model compounds, and several reports have appeared in the literature concerning anaerobic photolysis in protic and aprotic solvents of alkylcobaloximes with nitrogen and phosphorus donor bases. It has been demonstrated that the photolysis products of alkylcobaloximes with symmetric phosphorus donor bases are independent of the alkyl group and that at all temperatures irradiation gives rise to a cobalt(II) five-coordinate species and an organic radical, thus implying the homolytic cleavage of the Co−C bond …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cleavage of the cobalt−carbon bond, which is a central issue in B 12 chemistry, has been studied in model compounds, and several reports have appeared in the literature concerning anaerobic photolysis in protic and aprotic solvents of alkylcobaloximes with nitrogen and phosphorus donor bases. It has been demonstrated that the photolysis products of alkylcobaloximes with symmetric phosphorus donor bases are independent of the alkyl group and that at all temperatures irradiation gives rise to a cobalt(II) five-coordinate species and an organic radical, thus implying the homolytic cleavage of the Co−C bond …”
Section: Introductionmentioning
confidence: 99%
“…For alkylcobaloximes with nitrogen bases it has been reported that the products observed upon photolysis with visible light depend (a) on the ligand trans to the alkyl group, as it may induce deformations on the equatorial moiety that control the reactivity of the photolysis primary products, , and (b) on the alkyl group, as photolysis at 250 K of methyl- and benzylpyridinecobaloximes was claimed not to induce homolysis of the cobalt−carbon bond but reduction of the metal center. However, it must be pointed out that this conclusion was based on results obtained only for two compounds and that the analysis of the ESR spectra was controversial 6a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The primary step of this reaction is the formation of the methyl radical, which has been quenched with spin traps such as nitrosodurene or phenyl t-butyl nitrone. 39 Methyl radicals add to the β-position of alkyl methacrylates. The persistent cobaloxime(II) radical which is present in solution traps the adduct radical and regenerates the unsaturation in the product via hydridocobaloxime formation.…”
Section: Insertion Reactions Of Organocobalt(dmgh) 2 Complexesmentioning
confidence: 99%
“…To explore the origin of the DMPO-H adduct, perdeuterated acetaldehyde was oxidised in the presence of base and PI-Au catalyst. A DMPO-D adduct (a N = 14.54, a H = 18.79, a D = 2.84 G) 22 was observed, thus suggesting that the hydrogen adduct is formed as a consequence of C-H bond cleavage (see ESIw). Observation of a DMPO-H adduct in a related Au-catalysed alcohol oxidation reaction was recently attributed to the intermediate formation of Au-H as a consequence of hydride transfer from the C-H bond to gold.…”
mentioning
confidence: 99%